An integrated framework for implementing technology roadmapping in industry - Mejia Pantoja de Cavin, Shirley Gisela (2012)
Managing technological change in business is difficult. Especially for organisations in technology-based sectors where they are required to rethink and redesign their strategies to ensure they remain competitive in evolving markets.